2009
DOI: 10.1007/s00365-009-9068-9
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-Structured Preconditioners and Approximate Inverse of Elliptic Operators in ℝ d

Abstract: In the present paper we analyze a class of tensor-structured preconditioners for the multidimensional second-order elliptic operators in R d , d ≥ 2. For equations in a bounded domain, the construction is based on the rank-R tensor-product approximation of the elliptic resolvent B R ≈ (L − λI ) −1 , where L is the sum of univariate elliptic operators. We prove the explicit estimate on the tensor rank R that ensures the spectral equivalence. For equations in an unbounded domain, one can utilize the tensor-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 26 publications
0
63
0
Order By: Relevance
“…In general, the best R-term nonlinear approximation shows rather slow polynomial convergence in the rank parameter R, [92], and it can be calculated by the simple (but non-robust) greedy-type incremental algorithms. For the class of (physically relevant) analytic multivariate functions and Green's kernels the exponential convergence in the separation rank R can be proved [25,93,49,53,54], that leads to the asymptotically optimal bound on the canonical rank, R = O(log N ), implying the approximation rate O(N −α ), with α ≥ 1.…”
Section: Advances Of Tensor Methods In the Recent Decadementioning
confidence: 99%
See 3 more Smart Citations
“…In general, the best R-term nonlinear approximation shows rather slow polynomial convergence in the rank parameter R, [92], and it can be calculated by the simple (but non-robust) greedy-type incremental algorithms. For the class of (physically relevant) analytic multivariate functions and Green's kernels the exponential convergence in the separation rank R can be proved [25,93,49,53,54], that leads to the asymptotically optimal bound on the canonical rank, R = O(log N ), implying the approximation rate O(N −α ), with α ≥ 1.…”
Section: Advances Of Tensor Methods In the Recent Decadementioning
confidence: 99%
“…Fully tensorized numerical approach for solving the Hartree-Fock equation, discretized over N × N × N grid, by tensor truncated iteration of complexity O(N log N ), was recently presented in [58]. Other successful applications to high-dimensional eigenvalue problems [37,54] and to stochastic PDEs [64,62] are reported. A class of low tensor rank preconditioners for the multidimensional elliptic problems with jumping coefficients in R d is proposed in [18].…”
Section: On Tensor-structured Solution Of Multidimensional Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical analysis of the multilinear tensor product approaches for the treatment of some multivariate operators and functions arising in scientific computing was performed in [5,6,8,12]. The application of tensor decomposition algorithms to discretized multivariate functions and operators [10,14,13,11] showed that methods of multi-way analysis can be applied to the numerical solution of basic equations of mathematical physics placing stringent requirements upon the accuracy of results.…”
Section: Introductionmentioning
confidence: 99%